The "First Ones to Close and Last Ones to Re-Open". (22nd June 2022) - Kuchar, Robin; Frey, Maxine; Gooß, Julia; Mertens, Tim
Abstract : During the initial phase of the pandemic in the spring of 2020, music venues and clubs were the first to close—and often the last to re-open. Based on knowledge about music venues and club culture from the pre-COVID-19 era and data collected among club owners, clubbers, venue associations and cultural policy in Germany, this article encompasses a variety of perspectives regarding the situation of live music venues and clubs during the pandemic. Firstly, it analyses, from a German perspective, the club-related developments of the COVID-19 crisis from the first lockdown in March 2020 to the spring of 2021. Secondly, it considers the effect of "loss" among audiences and, thirdly, the discourse about cultural policy and emergency funds for music clubs and live music culture in Germany.